Utilizing the Local Environment as a Learning Resource in Science Education: A Systematic Literature Review - Muslihatun, Fitri; Zuriyatunnisa, Baiq (Indonesian Journal of Teacher Education, 2025)
Science learning requires concrete and contextual learning resources to support meaningful scientific understanding. This review aims to analyze the use of the natural environment as a learning resource in science education and to examine its implementation forms, learning impacts, and challenges faced by teachers. The study employed a Systematic Literature Review (SLR) method following the PRISMA protocol, focusing on relevant national publications from 2020 to 2025. The analysis indicates that the environment is utilized through observation activities, field-based experiments, and environmental science projects. These forms consistently contribute to improving students' conceptual understanding, science process skills, learning motivation, and ecological literacy. Environmental-based learning also helps students relate scientific concepts to real phenomena and increases their engagement in learning activities. However, its implementation still encounters challenges, including limited instructional time, teacher readiness, school environmental conditions, and the availability of authentic assessment tools. Overall, environmental-based learning has strong potential to enhance the quality of science education when systematically designed and supported by adequate facilities and school policies.